Coordinating Buyer-Seller Transactions Across Multiple Products - Kohli, Rajeev; Park, Heungsoo (Management Science, 1994)
Joint ordering policies are examined as a method for reducing the transactions cost for multiple products sold by a seller to a homogeneous group of buyers. The problem of determining efficient joint ordering policies has the same structure as the previously-examined problem of determining the efficient ordering policy for a single product. Efficient joint lot-sizes are independent of prices, and are supported by a range of average-unit prices that permit every possible allocation of the transactions-cost saving between the buyer and the seller. Product bundling supports efficient joint orders across products, just as a quantity discount supports efficient transactions for a single product.